Floristic Survey of Sagareshwar Wild Life Sanctuary, Maharashtra - Awale, Vikas; Bachulkar, Madhukar (Indian Forester, 2010)
Sagareshwar Wild Life Sanctuary is situated in Sangli district of Maharashtra State. The semi denuded hills and drought areas of Sagareshwar was declared as Sanctuary by the State Government in 1985,comprising 1087.75 ha. area. Sanctuary lies about 500 m amsl. It consists Southern tropical thorny type of forest. The present floristic work reports 356 species of angiosperm belonging to 254 genera and 79 families. Out of 356 species,314 species are dicots and 42 are monocots. The present paper includes notes on study area and status of the flora of Sanctuary.